Impact of the COVID‐19 pandemic on international cutaneous squamous cell carcinoma incidence: A systematic review and meta‐analysis - James Wall; Kieran Gadsby‐Davis; Khaylen Mistry; Nick J. Levell; Zoe C. Venables (Wiley, 2024)
Abstract Background Non‐melanoma skin cancer (NMSC) is the most common cancer globally in white ethinicity populations, and cutaneous squamous cell carcinoma (cSCC) is the second most common subtype. The COVID‐19 pandemic severely impacted public and private healthcare systems. Many studies have reported reduced cancer diagnoses during the pandemic. The impact of the COVID‐19 pandemic on global cSCC and NMSC incidence is poorly reported. Objectives The aim was to conduct a systematic review and meta‐analysis to assess the impact of the COVID‐19 pandemic on global cSCC and NMSC incidence rates, compared with 2019 incidence rates. Two primary outcome measures were used: crude incidence rate ratios (CIRR) and age‐standardised incidence rate ratios (ASIRR). Methods A structured search was undertaken on 23 March 2023 using grey literature and four electronic databases: MEDLINE, CINAHL, EMBASE and Web of Science. Studies published before January 2020 were excluded. A quality assessment was undertaken using A. Lomas quality assessment tool. CIRR outcomes were synthesised in a meta‐analysis, while ASIRR outcomes were narratively synthesised. Results Fourteen cancer registries were included, capturing data from 13 countries across Europe. Variation was observed in NMSC and cSCC incidence across the cancer registries. Pooled cSCC crude incidence rates in 2020 were equal to crude incidence rates in 2019 (cSCC‐CIRR 1.00 (95% confidence interval (CI) 0.94-1.06). In 2021, the pooled result indicated a non‐significant 8% increase in cSCC crude incidence rates, compared with 2019 (cSCC‐CIRR 1.08 (95% CI 0.98-1.19). Significant reductions were reported in NMSC incidence across all meta‐analyses in 2020 and 2021 compared with 2019. Heterogeneity was observed across most pooled estimates (I2>75%). Conclusion There was a lack of high quality data on cSCC incidence rates recorded during the pandemic outside of Europe. The COVID‐19 pandemic resulted in no significant changes in cSCC incidence across Europe. By contrast, NMSC incidence fell across Europe following the pandemic. Significant reductions in pooled NMSC incidence rates may reflect a delay in basal cell carcinoma presentation, diagnosis and treatment. Although annual incidence rates for cSCC were not affected by the pandemic, delays in treatment may still have occurred, which may result in poorer outcomes yet to be fully understood.